2022
DOI: 10.1038/s41415-022-3987-2
|View full text |Cite
|
Sign up to set email alerts
|

Unlocking the potential of NHS primary care dental datasets

Abstract: Introduction:Maximising the use of routinely-collected health data for research is a key part of the UK Government's Industrial Strategy. Rich data are generated by NHS primary care dental services, but the extent of their use in research is unknown. Aims:To profile the utility of the post-2006 NHS dental datsets for research, map how they have been used to date, and develop recommendations to maximise their utility. Methods:The content of and access to the four UK NHS dental datasets was collated using public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…One aspect we explored was the feasibility of using routinely held NHSBSA data for a primary outcome, and the reliability of linking personal identifiers collected in the urgent dental care setting. Relatively few trials have made use of these data in England [ 22 ], and although we experienced a relatively high matching rate, we identified that by adding postcode as an additional identifier, this could be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect we explored was the feasibility of using routinely held NHSBSA data for a primary outcome, and the reliability of linking personal identifiers collected in the urgent dental care setting. Relatively few trials have made use of these data in England [ 22 ], and although we experienced a relatively high matching rate, we identified that by adding postcode as an additional identifier, this could be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…One aspect we explored was the feasibility of using routinely held NHSBSA data for a primary outcome, and the reliability of linking personal identi ers collected in the urgent dental care setting. Relatively few trials have made use of these data in England, 21 and although we experienced a relatively high matching rate, we identi ed that by adding postcode as an additional identi er, this could be further improved.…”
Section: Discussionmentioning
confidence: 99%
“…Routinely collected NHS dental claims data offered an innovative solution but have been a relatively underused resource for research, particularly in comparison to other NHS activity data sets, for example, Hospital Episode Statistics (HES), or the general medical practice-based Clinical Practice Research Datalink database. 165 In working with NHS BSA we have increased our knowledge and understanding of the potential for these data sets to be used for research. These reflections inform our recommendations for the further development of these data sets, and the utility of NHS dental data sets across the four UK home countries has been explored in more detail in a separate paper.…”
Section: Strengthsmentioning
confidence: 99%
“…These reflections inform our recommendations for the further development of these data sets, and the utility of NHS dental data sets across the four UK home countries has been explored in more detail in a separate paper. 165 The benefits of using these routinely collected data are that very large samples are available and the data provide an ability to follow patients over long time periods. Once the necessary permissions are secured, the data are available at minimal costs and within a relatively short time frame.…”
Section: Strengthsmentioning
confidence: 99%
See 1 more Smart Citation